Effects of β-glucan extracted from Agaricus blazei on the expression of ERCC5, CASP9, and CYP1A1 genes and metabolic profile in HepG2 cells - Da Silva, A. F.; Sartori, D.; MacEdo, F. C.; Ribeiro, L. R.; Fungaro, M. H P; Mantovani, M. S. (SAGE Publications, 2013)
The polysaccharide β-glucan has biological properties that stimulate the immune system and can prevent chronic pathologies, including cancer. It has been shown to prevent damage to DNA caused by the chemical and physical agents to which humans are exposed. However, the mechanism of β-glucan remains poorly understood. The objective of the present study was to verify the protective effect of β-glucan on the expression of the genes ERCC5 (involved in excision repair of DNA damage), CASP9 (involved in apoptosis), and CYP1A1 (involved in the metabolism of xenobiotics) using real-time polymerase chain reaction and perform metabolic profile measurements on the HepG2 cells. Cells were exposed to only benzo[a]pyrene (B[a]P), β-glucan, or a combination of B[a]P with β-glucan. The results demonstrated that 50 μg/mL β-glucan significantly repressed the expression of the ERCC5 gene when compared with the untreated control cells in these conditions. No change was found in the CASP9 transcript level. However, the CYP1A1 gene expression was also induced by HepG2 cells exposed to B[a]P only or in association with β-glucan, showing its effective protector against damage caused by B[a]P, while HepG2 cells exposed to only β-glucan did not show CYP1A1 modulation. The metabolic profiles showed moderate bioenergetic metabolism with an increase in the metabolites involved in bioenergetic metabolism (alanine, glutamate, creatine and phosphocholine) in cells treated with β-glucan and to a lesser extent treated with B[a]P. Thus, these results demonstrate that the chemopreventive activity of β-glucan may modulate bioenergetic metabolism and gene expression. © 2013 The Author(s).
Keywords: β-glucan; CASP9; CYP1A1; ERCC5; gene expression; alanine; benzo[a]pyrene; beta actin; beta glucan; caspase 9; creatine; cytochrome P450 1A1; excision repair cross complementing protein 5; glutamic acid; phosphorylcholine; unclassified drug; Agaricus blazei; bioenergy; cell strain HepG2; chemoprophylaxis; drug cytotoxicity; energy metabolism; gene repression; genetic transcription; human; human cell; human tissue; nonhuman; priority journal; real time polymerase chain reaction; xenobiotic metabolism